English learning burnout: Scale validation in the Chinese context - Liu, Honggang; Zhong, Yuchen (Frontiers in Psychology, 2022)
While the research on learning burnout has been well conducted in educational psychology, it has received little concern in the field of language education. To fill this gap, the present study aims at exploring the construct of English learning burnout (ELB) and examining the levels of this complex construct in a large sample of 1,213 Chinese senior high school students utilizing a 15-item Senior High school English Learning Burnout Scale. A two-dimension structure of ELB, namely, Exhaustion and Demotivation, was extracted by the exploratory factor analysis and validated by confirmatory factor analysis. Descriptive analysis showed low levels of global ELB and Exhaustion and a moderate level of Demotivation. It proposed that the teachers should be aware of fostering students’ self-regulated strategies to alleviate students’ ELB.